The Globalization of LGBT Identity and Same-Sex Marriage as a Catalyst of Neo-institutional Values: Singapore and Indonesia in Focus - Yulius, H.; Tang, A.; Offord, Baden (Springer Link, 2018)
The focus of this chapter is on the institutional and state responses and reactions to issues of same-sex marriage and analytics of the relationship between state, civil society institutions, and international humanitarian organizations in two neighboring countries in Southeast Asia: Singapore and Indonesia. Each country has specific colonial histories, ethnic, religious, social, and cultural conditions and explicitly shows the negotiations of the social-cultural boundaries formed around non-normative genders and sexualities, particularly after the institutionalization of same-sex marriage. The Indonesian and Singaporean stories offer exemplary cases of discursive institutionalization of gendered and sexualized subjects in contradistinction to the globalized world of lesbian, gay, bisexual, and transgender (LGBT) identities and increasing jurisdictions where same-sex marriage has become legal. As such identities globalize and begin to be institutionalized, a series of counter-reactions has followed and subsequently produced unexpected outcomes.